ERP OPEN SOURCE APACHE OFBIZ - Prakarsa A.S, Muhammad (Jurnal E-Komtek (Elektro-Komputer-Teknik), 2018)
The integrated information system has become very important and urgent to be implemented, to support and determine the business strategy further to lead for having company superiority in anticipating business competition. The presence of information system, specifically based on ERP could contribute to anticipate business competition and to determine business strategy. These could lead management team to be more focus on creating innovation for the company improvement and having maximum profit. Thus the synchronization between the improvement of ERP system and business strategy is very important to support the development of company business on its short term period and long term period. Open Source is the right answer for the choice considering that the complex market necessity and its citizen ‘s habit that always hope for operating and using anything for free